Clinical evaluation of hyperimmune plasma for treatment of dogs with naturally occurring parvoviral enteritis. Issue 5 (24th July 2020) - Acciacca, Rachel A.; Sullivan, Lauren A.; Webb, Tracy L.; Johnson, Valerie; Dow, Steven W.
Abstract: Objective: To evaluate the clinical efficacy of a single infusion of hyperimmune plasma (HIP) in dogs with canine parvovirus (CPV). Design: Prospective, randomized, placebo‐controlled clinical trial. Setting: University teaching hospital. Animals: Client‐owned dogs with naturally occurring CPV. Interventions: Dogs presenting for CPV treatment (n = 31) underwent cardiovascular resuscitation and were randomized to receive a single dose of either HIP (10 mL/kg IV) or placebo (0.9% sodium chloride [10 mL/kg IV]) during the first 6 hours of hospitalization. All dogs were treated with a standardized treatment protocol (IV fluid therapy [120 mL/kg/d isotonic crystalloids], cefoxitin [30 mg/kg IV q 8 h], maropitant [1 mg/kg IV q 24 h], and buprenorphine [0.01–0.02 mg/kg IV q 8 h]) until hospital discharge. Measurements and main results: Dogs treated with HIP (n = 16) demonstrated a lower shock index at 24 hours (median = 0.77, range: 0.5–1.5) than those treated with placebo (n = 15, median = 1.34, range: 0.5–1.7; P  = 0.02). Plasma lactate concentration was lower at 24 hours in HIP‐treated dogs (median = 1.3 mmol/L, range: 0.9–3.4 mmol/L) than in placebo‐treated dogs (median = 2.1 mmol/L, range: 1.1–3.4 mmol/L; P  = 0.01). There was no difference in duration of hospitalization when comparing HIP‐treated dogs (median = 3.2 days, range: 0.83–10 days) to placebo‐treated dogs (median = 2.83 days, range: 1–8.38 days; P  = 0.35). Survival was 16 of 16 (100%) for the HIP group and 14 of 15 (93.3%) for the placebo group ( P  = 0.32). Conclusions: HIP at 10 mL/kg IV administered to dogs with CPV within the first 6 hours of hospitalization improves markers of shock during the initial 24 hours of hospitalization. No effects were observed on duration of hospitalization or mortality; however, this study was underpowered to evaluate these effects. HIP was well tolerated in this population of critically ill dogs.